2021
DOI: 10.4274/bmb.galenos.2021.04.050
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of COVID-19 Pandemic on Depression, Anxiety and Stress Levels of Pregnant Women

Abstract: Coronavirus disease-2019 (COVID-19) pandemic has negatively affected the psychology of the society. In this study, it was aimed to determine the stress, anxiety and depression levels in pregnant women during the COVID-19 pandemic and to investigate the delivery method attitudes using various scales. Method:The study included 151 pregnant women admitted to the obstetrics and gynecology clinic of our tertiary hospital for follow-up. A 31-question questionnaire containing demographic information and questions ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…15,16 There is also increase in the frequency of anxiety and depression, the mechanism of which is uncertain. 17 Epidemiological, clinical and experimentally, studies has shown that COVID-19 patients have a higher risk of thromboembolic events, including neurovascular diseases, in the acute phase of infection. 18,19 In a recently published, prospective, multinational study, 123 (0.7%) cases presenting with acute ischemic stroke were reported in a total of 17,799 SARS-CoV-2 infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 There is also increase in the frequency of anxiety and depression, the mechanism of which is uncertain. 17 Epidemiological, clinical and experimentally, studies has shown that COVID-19 patients have a higher risk of thromboembolic events, including neurovascular diseases, in the acute phase of infection. 18,19 In a recently published, prospective, multinational study, 123 (0.7%) cases presenting with acute ischemic stroke were reported in a total of 17,799 SARS-CoV-2 infected patients.…”
Section: Discussionmentioning
confidence: 99%